Decision-making issues related to the surgical treatment 'of congenital malformations of the Central Nervous System - Di Rocco, Concezio (Medicina e Morale, 2024)
Current methods of diagnosis allow the early detection of foetal malformations; in non-exceptional cases, where such malformations constitute developmental pathological conditions, there is a need to consider a possible therapeutic decision. Although apparently this type of decision appears to present very particular aspects, in reality the ethical problem arising from it does not differ substantially from the general one always faced by doctors when faced with patients whose treatment appears difficult and in whom the therapeutic outcome is not always predictable.